Fludarabine phosphate: A new active agent in hematologic malignancies - Keating, M.J.; O'Brien, S.; Plunkett, W.; Robertson, L.E.; Gandhi, V.; Estey, E.; Dimopoulos, M.; Cabanillas, F.; Kemena, A.; Kantarjian, H. (Seminars in Hematology, 1994)
Fludarabine is the most active single agent that has been studied in CLL. The response rate for both previously untreated and previously treated patients is higher than combinations that have been studied. Myelosuppression is dose-limiting with substantial evidence of suppression of normal T- lymphocytes, both in patients receiving fludarabine as a single agent and in patients being treated with fludarabine plus prednisone. Along with the myelosuppression noted in advanced stage disease, infections are the most common complication with many of the infections being associated with T-cell immunodeficiency rather than the more traditional characteristics of neutropenia and hypogammaglobulinemia. Comparative clinical trials are being conducted in Europe with a cyclophosphamide, doxorubicin, prednisone regimen in previously untreated and previously treated patients. In the United States, previously untreated patients are being entered in a trial comparing fludarabine with chlorambucil alone or the combination of fludarabine and chlorambucil. The eventual contribution of fludarabine to the management of chronic lymphocytic leukemia awaits the conclusion of these clinical trials.